Orientação a stakeholders das cooperativas: um estudo quantitativo - Rocha, Marcos Vinícius Monteiro da (2023)
Using Freeman's (1984) stakeholder theory as a reference, the study measured the stakeholder orientation of cooperatives by employing the stakeholder salience theory. Data was collected through an online questionnaire directed at top-level managers of the organization. The data analysis will be conducted using a Bayesian regression model that utilizes the independent variable to understand managers' perception of the influence of their stakeholders through their attributes. Additionally, as a moderating variable, the quantification of a positive trend towards some of the presented organizational culture models will be considered. The study aims to contribute by identifying the relevance given by cooperatives to their stakeholders and presenting a sample scenario of Brazilian cooperatives and their behavior within their context.